Natal teeth associated with Riga-Fede ulcer: case report - Danelon, Marcelle; Emerenciano, Nayara Gonçalves; Garcia, Luhana Gonzales; Percinoto, Célio; Cunha, Robson Frederico (ARCHIVES OF HEALTH INVESTIGATION, 2017)
Aim: Was to report a case report showing the occurrence of natal teeth associated with Riga-Fede ulcer, clinical implications and treatment approach. Case report: Two-month-old female patient, was taken by his mother to the Baby Clinic of the Araçatuba Dental School, Univ. Estadual Paulista (UNESP) - Department of Pediatric Dentistry and Public Health-Brazil, reporting ulcer in the womb of tongue and weight loss. On clinical examination, there was teeth in the region of the mandibular incisors and in the ventral region of the tongue, characterized as Riga-Fede ulcer. In the radiographic examination it was noted that the same was supernumerary. After clinical and radiographic examinations, we opted for the natal teeth exodontics. After thirty days, the mother informed us that the ulcer disappeared and the child returned to feed, demonstrating that the approach has proved suitable and effective. Conclusions: Natal teeth supernumerary when related the Riga-Fede ulcer should be extracted; It should not be neglect weight loss in infants and treatment aims at healing of the lesion feed return and weight gain. Descriptors: Natal Teeth; Oral Ulcer; Tongue Diseases.